Abdominal radical trachelectomy--technique and experience - Cibula, D; Ungár, L; Svárovský, J; Zivný, J; Freitag, P (Ceská gynekologie, 2005)
Discussion of current experiences with abdominal radical trachelectomy in the treatment of early stages of cervical cancer in fertile women. Case-reports. Department of Obstetrics and Gynecology, General Faculty Hospital and 1st Medical Faculty, Charles University, Prague. Presentation of 4 cases of abdominal radical trachelectomy and pelvic lymphadenectomy. Discussion with published data. Three cases of open abdominal and one case of laparoscopic abdominal radical trachelectomies together with pelvic lymphadenectomies are presented. All procedures were indicated for cervical cancer stages IA2-IB1. Frozen section of pelvic nodes and a slice of upper margin of cervix revealed no metastasis or infiltration. In total 22-43 pelvic nodes were removed, being negative in all cases. Operative time ranged between 148 and 270 min. in laparotomy and 250 min. in laparoscopy. Blood loss reached 350-3500 ml. There were no intraoperative complications, postoperatively one case of bladder atony was treated by suprapubic drainage for 30 days, one case of ileus was managed pharmacologically. Vaginal suture healed properly in all cases. No complications occurred within limited follow-up of 1-5 months. Abdominal radical trachelectomy with pelvic lymphadenectomy is a rational alternative in the treatment of stages IA2-IIA cervical cancer in women of fertile age. Standard radicality in parametria resection and easy incorporation into armamentarium of oncogynecological centers are main advantages of such approach. Laparotomy can be avoided using laparoscopy.